Losing one’s head. The exemplary figures of Isabella and Bradamante and their audience (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
The essay addresses the aspect of the representation of the feminine in Orlando Furioso that concerns sexual conduct and chastity. At the centre of my work is the reading of a series of episodes belonging to adjacent groups of cantos: the specular and conjoined events of Angelica and Olimpia in Cantos VIII-XII and the story of Isabella in Canto XIII; Isabella’s death at the hands of Rodomonte in Canto XXIX, and Bradamante’s revenge on her in Canto XXXV. The figures of Isabella and Bradamante construct the image of warrior women who are self-sufficient in the pursuit of virtue. For the female audience, the two figures build the possibility of autonomous preservation of chastity, immune from slander and suspicion; for the men, their example reassures the certainty of lineage. In the background, we also glimpse pagan warriors, first and foremost Rovenza, who brings the knot of chastity and reproduction into her story.
Keywords: Women; Orlando furioso; chastity; sexual behaviour; Bradamante; Isabella; genealogy